EFEKTIVITAS PEMBERIAN KOMPRES DAUN JARAK DAN BERAS UNTUK MENURUNKAN SUHU TUBUH ANAK PADA KASUS HIPERTERMI - Wasliah, Indah; Yolanda, Henny; Pratiwi, Eka Adithia; Syamdarniati, Syamdarniati; Rhomadonika, Fitri (MAJU : Indonesian Journal of Community Empowerment, 2024)
Hyperthermia is a condition where the body temperature increases, which can be dangerous if not treated properly. The use of compresses as a method of reducing body temperature is a concern. Fever is a change in condition from healthy to sick causing the body's reaction to increase the temperature, where the body temperature is higher than 37.5°C. There are several ways to reduce and control fever which can be done, one of which is non-pharmacological, namely by giving a compress, one method of compressing is by giving a compress with castor leaves and several grains of rice. Castor leaves compress is known to be effective in reducing children's fever because of its content. compounds such as phenols, flavonoid saponins and alkaloid compounds. Jatropha leaves also contain active compounds such as flavonoids, saponins, glycosides, alkaloids, quercetin, polyphenolic compounds and stredoids while soaked rice is very effective in accelerating the release of heat from the body because it contains nutrients, namely amino acids, vitamin B, vitamin E, minerals and antioxidant substances